PERFORMATIF BAHASA RITUAL CUCURANGI TOGO LASALIMU DALAM PEMBELAJARAN BAHASA INDONESIA BERBASIS BUDAYA LOKAL - Harun Harun; Hari Windu Asrini (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
This research is motivated by the increasingly eroded existence of local ritual languages ​​due to the currents of globalization and modernization of community communication patterns. The focus of the problem in this research is directed at a descriptive analysis of the form and performative function of speech acts in the Cucurangi Togo rite of the Lasalimu community, Buton Regency, and its formulation as a contextual teaching resource. Using a qualitative approach with a linguistic ethnography design, the important stages in this research are carried out systematically through participatory observation of the sacred stone object of Wacukamboy, in-depth interviews with nine key informants, textual transcription, pragmatic classification, and anthropolinguistic interpretation. The research findings reveal that this five-year oral tradition is dominated by declarative and imperative utterances that have multidimensional performative functions. The locutionary, illocutionary, and perlocutionary structures contained therein do not merely convey verbal information, but embody spiritual-social actions in the form of collective salvation prayers, rituals asking for forgiveness (somba waopu), and strengthening integrative cohesion (may topoose-ose). The main conclusion confirms that the ritual language of Cucurangi Togo is highly valid and effective when integrated as a local wisdom-based Indonesian language instructional medium in schools. This traditional instrument is highly relevant for supporting pragmatics materials, cultural description texts, and strengthening the pillars of religious character education in students on an ongoing basis. ABSTRAK Penelitian ini dilatarbelakangi oleh semakin terkikisnya eksistensi bahasa ritual lokal akibat arus globalisasi dan modernisasi pola komunikasi masyarakat. Fokus masalah dalam riset ini diarahkan pada analisis deskriptif mengenai bentuk dan fungsi performatif tindak tutur dalam ritus Cucurangi Togo masyarakat Lasalimu, Kabupaten Buton, serta formulasinya sebagai sumber ajar kontekstual. Menggunakan pendekatan kualitatif dengan desain etnografi linguistik, tahapan penting dalam penelitian ini dijalankan secara sistematis melalui observasi partisipatif pada objek batu keramat Wacukamboy, wawancara mendalam bersama sembilan informan kunci, transkripsi tekstual, klasifikasi pragmatik, hingga interpretasi antropolinguistik. Temuan riset menyingkapkan bahwa tradisi lisan lima tahunan ini didominasi oleh tuturan deklaratif dan imperatif yang memiliki fungsi performatif multidimensional. Struktur lokusi, ilokusi, dan perlokusi yang terkandung di dalamnya tidak sekadar menyampaikan informasi verbal, melainkan mengejawantahkan tindakan spiritual-sosial berupa doa keselamatan kolektif, ritual permohonan ampun (somba waopu), serta penguatan kohesi integratif (may topoose-ose). Simpulan utama menegaskan bahwa bahasa ritual Cucurangi Togo sangat valid dan efektif diintegrasikan sebagai media instruksional Bahasa Indonesia berbasis kearifan lokal di sekolah. Perangkat tradisi ini sangat relevan untuk menyokong materi pragmatik, teks deskripsi budaya, serta penguatan pilar pendidikan karakter religiusitas peserta didik secara berkelanjutan.